2008
DOI: 10.1111/j.1600-079x.2007.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of melatonin to treat surgical stress after major vascular surgery – a safety study

Abstract: Surgery for abdominal aortic aneurysm is associated with elevated oxidative stress. As an antioxidant in animal and human studies, melatonin has the potential of ameliorating some of this oxidative stress, but melatonin has never been administered to adults during surgery for the purpose of reducing oxidative damage. The aim of this pilot study was to evaluate the safety of various doses of melatonin administered during or after surgery and to monitor the changes in biomarkers of oxidative stress and inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 37 publications
(72 reference statements)
2
38
0
Order By: Relevance
“…Numerous clinical studies have documented improved sleep quality following administration of exogenous melatonin [1,3,4]. Recent studies also demonstrate analgesic [4,5], anxiolytic [5], anti-inflammatory [6], and anti-oxidative effects [6,7] of melatonin.…”
Section: Introductionmentioning
confidence: 94%
“…Numerous clinical studies have documented improved sleep quality following administration of exogenous melatonin [1,3,4]. Recent studies also demonstrate analgesic [4,5], anxiolytic [5], anti-inflammatory [6], and anti-oxidative effects [6,7] of melatonin.…”
Section: Introductionmentioning
confidence: 94%
“…This agent must be given intravenously and it has significant side effects, the most noteworthy of which is transient hypotension and emesis [103,104]. This contrasts with melatonin, since numerous studies in animals and man have revealed that melatonin has no acute or chronic toxicity [8,[105][106][107][108] even when the indoleamine is given during pregnancy [109]. Also, given the toxicity of WR-2171 it generally would not be considered useful for long term therapy; rather, its typical use is as a single administration therapy to be taken in advance of an intense radiation exposure to prevent the initial free radical damage meted out by the high dose ionizing radiation.…”
Section: Melatonin: Comparison With Other Radioprotectorsmentioning
confidence: 99%
“…In a later clinical trial, patients who received daily rectal melatonin treatment at a higher dose (300 mg per day) also did not show any complications [156]. A recent report also demonstrated that treatment of patients undergoing major aortic surgery with up to 60 mg intravenous melatonin during surgery was safe and without complications [151]. Therefore, application of a high pharmacological dose of melatonin in the therapy of autoimmune diseases should be acceptable.…”
Section: The Future Application Of Melatonin Treatment In Autoimmumentioning
confidence: 99%